IMPLEMENTASI PEMBINAAN KARAKTER ISLAMI PEDULI LINGKUNGAN DI SMPN 2 KESAMBEN JOMBANG - Alviana Dwi Marlita; Jumari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how the Adiwiyata program contributes to the development of environmental‑care character among students at SMP Negeri 2 Kesamben, Jombang. The research addresses declining ecological awareness among youth and investigates whether school‑based environmental policies, curriculum integration, participatory activities, and environmentally friendly facilities effectively foster attitudes and behaviors such as responsibility, discipline, waste management, and creative waste utilization. These character-building activities are also integrated with Islamic values emphasizing cleanliness, responsibility, stewardship of nature, and moral habituation in students’ daily school life. A qualitative case study design was employed, using semi‑structured interviews with key informants, participant observation of school practices (e.g., piket, waste sorting, tree planting, and “Jumat Bersih”), and document analysis to capture the four core components of Adiwiyata. Findings indicate that systematic habituation, teacher role modeling, and curricular integration significantly enhance students’ environmental care, while limitations in facilities, inconsistent staff commitment, and constrained instructional time hinder program sustainability. The study recommends strengthening institutional policies, improving waste‑management infrastructure, providing ongoing teacher training, and instituting regular monitoring and evaluation to sustain behavioral change. Results suggest that a coordinated combination of policy, pedagogy, and practice can make Adiwiyata a replicable model for character education grounded in environmental stewardship.